Wits and Interpretation : Keyboard Thoughts. - Edlund, Bengt (Frankfurt a.M. : Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2023)
This book offers critical demonstrations of various methods and concepts currently used in music analysis. Among the subjects are musical implications, tonal analysis, generative theory, ambiguity, similarity, and the key criteria met with in lawsuits of plagiarism. Finally, can a composer's sexual leanings be derived from his music?.
Options of continuation -- the first part of the prelude -- The second part of the prelude -- Interdependence and constraints -- consistency -- The influence of interpretation on form -- Elements of variation -- Chapter 13 Interpretation as continuation -- Introduction -- Some preliminary observations on the Brahms Intermezzo -- The first thematic period -- The second thematic period -- The middle section -- The stringendo episodes -- Concluding remarks -- Chapter 14 Musical dialogue in a Romantic violin sonata -- Impersonation and dialogue in music -- Structural dialogue in Brahms's Violin Sonata Op. 100 -- The first theme - initial statement -- The first theme - second statement and transition -- The second-theme episodes, the piano interlude, and the transition -- The third theme and the transition to the development -- Expressing a sense of dialogue -- Cues for a sense of dialogue in performances of the sonata -- Conclusions -- Chapter 15 Chopin themes -- Introduction -- A theme starting seven times -- An introductory theme and its culminating return -- A bass theme and its possible sequel -- The Three D1's -- Chapter 16 Keyboard commentaries on K. 282 -- Introduction -- Youthful mistakes -- The main theme -- The first phrase -- A sense of elision? -- The second phrase -- metric peculiarities and virtual delays -- The second phrase -- linear connections -- The Coda - the main theme revisited -- Formal variety and matters of transition -- Inherent tempo shifts -- Ornamentation -- Matters of performance -- The theme as a tonal hierarchy -- Tensions in tonal space -- attractions and yearning -- A bottom/up implicational analysis -- Remarks on Meyer's commentary -- A gambit and the Gambit -- Music examples -- References -- Bibliography.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books